2011
DOI: 10.1063/1.3580765
|View full text |Cite
|
Sign up to set email alerts
|

Near 1 V open circuit voltage InAs/GaAs quantum dot solar cells

Abstract: Ten-layer InAs/GaAs quantum dot (QD) solar cells exhibiting enhanced short circuit current (Jsc) and open circuit voltage (Voc) comparable to a control GaAs p-i-n solar cell are reported. 1 sun Jsc is enhanced by 3.5% compared to that of the GaAs control, while the Voc is maintained at 994 mV. Results were achieved using optimized InAs QD coverage and a modified strain balancing technique, resulting in a high QD density (3.6×1010 cm−2), uniform QD size (4×16 nm2), and low residual strain (103 ppm). This enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
141
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(149 citation statements)
references
References 20 publications
4
141
0
4
Order By: Relevance
“…QDs of the desired size (down to 2-3 nm) have been produced through this technique 50 and can be implemented with several material options that give a bandgap distribution close to the optimum value of 1.95 eV, with good lattice matching. Nevertheless, some carefully manufactured InAs/GaAs cells have already presented minor voltage reductions 18,19 and are therefore probably already operating as IB cells at room temperature.…”
Section: Summary and Challengesmentioning
confidence: 99%
“…QDs of the desired size (down to 2-3 nm) have been produced through this technique 50 and can be implemented with several material options that give a bandgap distribution close to the optimum value of 1.95 eV, with good lattice matching. Nevertheless, some carefully manufactured InAs/GaAs cells have already presented minor voltage reductions 18,19 and are therefore probably already operating as IB cells at room temperature.…”
Section: Summary and Challengesmentioning
confidence: 99%
“…Many efforts are being made to avoid voltage degradation of the IBSCs and promising results have been obtained [10,11]. It has been demonstrated that, at RT, the thermal carrier escape from the IB to the CB dominates the extraction of photocurrent [12].…”
Section: Introductionmentioning
confidence: 99%
“…We believe this continuum tailing states superposed with QD and WL induced confined energy states within the forbidden band function as an efficient carrier relaxation and collection pathway [6][7][8] . A slight enhancement of Jsc, accompanied by a degradation of Voc [6][7][8][9][10][11][12] , under one sun illumination and room temperature conditions can be completely explained by a single-photon absorption process via below-bandgap states including both quantum confined states and tailing states. The degradation of Voc is related to an increased dark current resulting from a direct carrier collection/relaxation via the tailing states.…”
mentioning
confidence: 99%